Demographic Summaries for English-speaking Populations Across Quebec's RTS Territories (2011) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
This document contains a series of one-page summaries highlighting the key demographic characteristics of the English-speaking populations for each of the new health territories established by the MSSS in 2015 as part of the re-organization of health services. The 25 health geographies in this series are the RTS which is the French-language acronym for the Réseau territoriale des services which correspond to the CISSS and CIUSSS territories. This series is intended as a knowledge resource for the CHSSN NPI networks.

2015 CHSSN-CROP Survey on Community Vitality : Findings on English-speaking Community Vitality Across Key Sectors - Pocock, Joanne (Community Health and Social Services Network, 2016)
This 2015-2016 Baseline Data Report relays key findings of the 2015 CHSSN/CROP Survey on Community Vitality as they unfold across key sectors. The commonalities and distinct features of regional communities within the English-speaking provincial population are delineated as well as sub-groups defined by gender, age, household income and level of bilingualism. This report from the 2015 survey is intended as a companion to the 2015-2016 Baseline Data Report entitled English Language Access to Health and Social Services in Québec, which includes a summary of results from Focus Group sessions conducted in several regions around the province.

Baseline Data Report 2015-2016 : English-language Health and Social Services Access in Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
This 2015-2016 Baseline Data Report relays the health and social service findings of the 2015 CHSSN/CROP Survey on Community Vitality. The commonalities and distinct features of regional communities within the English-speaking provincial population are delineated as well as sub-groups defined by gender, age, household income, health status and level of bilingualism. While this report is limited to the health and social service sector, the Survey on Community Vitality (2005, 2010, and 2015) also collects the opinions, perceptions and expectations of a representative sample of English-speaking Quebecers in most regions of Quebec with respect to issues in education, human resource development, justice, culture and communications. The 2015 study replicates previous surveys conducted by CROP in 2000 for the Missisquoi Institute and again in 2005 and 2010 for the CHSSN.
Keywords: Official Language Minority Community (OLMC)

Programme d’accès : aux services de santé et aux services sociaux en langue anglaise pour les personnes d’expression anglaise de la Capitale-Nationale : 2012-2015 - Laroche, Daniel; Blais, Sébasitien; Paquette, Brigitte (Centre intégré universitaire de santé et de services sociaux de la Capitale Nationale, 2016)
En décembre 2015, le ministère de la Santé et des Services sociaux (MSSS) demandait au Centre intégré universitaire de santé et de service sociaux de la Capitale-Nationale de procéder à une mise à jour du Programme d’accès aux services de santé et aux services sociaux en langue anglaise pour les personnes d’expression anglaise 2012-2015 (programme d’accès) de leur région respective. Le dernier programme d’accès élaboré par l’Agence de la santé et des services sociaux de la Capitale- Nationale avait fait l’objet d’une approbation par le Ministère en 2012. La démarche de mise à jour vise un portrait actuel des services de santé et des services sociaux en langue anglaise considérant le contexte actuel de la réorganisation du réseau de la santé et des services sociaux entamé depuis l’adoption de la LMRSSS, Loi modifiant l’organisation et la gouvernance du réseau de la santé et des services sociaux notamment par l’abolition des agences régionales.

Trousse : Vous devez vous déplacer pour des soins de santé? - Committee for Anglophone Social Action (CASA); Council for Anglophone Magdalen Islanders (CAMI); Vision Gaspé-Percé Now; Centre integré de santé et de services sociaux de la Gaspésie (2016)

English-language Interpretation Services to Improve Language Access to Health and Social Services for Members of English-speaking Communities in Quebec : Status Report - Kosseim, Myléne (Community Health and Social Services Network (CHSSN), 2016)
This study aims to document the current situation regarding the use of formal interpreters as a means of language access to health and social services for English-speaking persons and to propose possible improvements to the Ministère de la Santé et des Services sociaux.
Keywords: Official Language Minority Community (OLMC)